2009
DOI: 10.1007/s00134-009-1427-2
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood pressure during early sepsis and outcome

Abstract: Objective: To evaluate the association between arterial blood pressure (ABP) during the first 24 h and mortality in sepsis. Design: Retrospective cohort study. Setting: Multidisciplinary intensive care unit (ICU). Patients and participants: A total of 274 septic patients. Interventions: None. Measurements and results: Hemodynamic, and laboratory parameters were extracted from a PDMS database. The hourly time integral of ABP drops below clinically relevant systolic arterial pressure (SAP), mean arterial pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
142
4
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(157 citation statements)
references
References 27 publications
7
142
4
4
Order By: Relevance
“…Both studies showed a correlation between MAP thresholds and survival [3,4] and organ dysfunction [4,5]. Best results were seen with a MAP between 60 and 65 mmHg, and the time spent below these values correlated with risk of mortality [3,4].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Both studies showed a correlation between MAP thresholds and survival [3,4] and organ dysfunction [4,5]. Best results were seen with a MAP between 60 and 65 mmHg, and the time spent below these values correlated with risk of mortality [3,4].…”
mentioning
confidence: 93%
“…MAP is a key component of tissue perfusion and is often viewed as a surrogate of organ perfusion pressure. Both the SSC and ESICM guidelines suggest keeping MAP ≥ 65 mmHg and individualizing this target based on comorbidities.The current MAP target of 65 mmHg is mainly based on the results of two retrospective studies investigating sequential MAP readings and the time spent below different threshold values of MAP during the first 24 or 48 h of management of patients with septic shock [3,4]. Both studies showed a correlation between MAP thresholds and survival [3,4] and organ dysfunction [4,5].…”
mentioning
confidence: 99%
“…The relationship between hypotension and the outcome of severe sepsis has been extensively examined in several reports because the definition of septic shock includes hypotension after fluid resuscitation 8, 9, 15. Nevertheless, as far as we know, there have been no reports similar to the current one that focus on initial hypotension as the predictive outcome measure for patients with severe sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent risk factor for ICH is chronic hypertension,24, 25 which also causes a rightward shift in the renal autoregulation curve26 and increases the threshold value of mean arterial pressure needed to maintain renal perfusion 27, 28. Drastic and rapid lowering of blood pressure may also shift the renal autoregulation curve rightward9 and create a new less robust limit, where even nonhypotensive or normotensive blood pressures decrease renal blood flow and exacerbate renal injury.…”
Section: Discussionmentioning
confidence: 99%